Conceptual model of a semi-arid coastal aquifer using hydrogeochemical seasonal variation and isotopic fingerprints in Tamoios, Rio de Janeiro, Brazil - Sabino, Hullysses; Silva, Gerson C.; Costa, Vladimir E. [UNESP]; Menezes, Juliana (Springer Nature, 2023)
The present study focuses on the Tamoios aquifer (Rio de Janeiro State, Brazil), which is under pressure due to receiving a significant volume of urban runoff and sewage. The objective was based on a number of hydrogeochemical and isotope data to assess the aquifer functioning and establishing a conceptual model to evaluate the hydrogeochemical processes. The database consisted of groundwater samples (n = 20) and surface water samples (fluvial, lagoon, and seawater) (n = 4), analyzed for major and trace constituents plus 18O and 2H isotopes. Results demonstrate that most of the groundwater samples were classified as sodium-chloride type in the rainy season and magnesium-chloride type in the dry season. Ion ratios indicated the ion sources and chemical behavior. Groundwater remained with a relatively high salt content throughout the seasons, particularly in the samples from the southern portion of the aquifer. PHREEQC software simulations exposed dolomite and calcite in mostly undersaturated condition and halite subsaturated throughout the year. Hydrogeochemical behavior indicated the salt content in the groundwater was not related to a hypothetical saltwater intrusion and revealed a steady state condition for the groundwater interface. Groundwater samples have a similar isotopic signature and were likely influenced by evaporative effects, indicating a role for the existing ponds in aquifer recharge. Strong free surface evaporation effects, evapotranspiration, and drainage processes in the floodplains probably enhanced the high ionic concentration in the groundwater environment.
Keywords: Environmental isotopes; Groundwater conceptual model; Hydrogeochemistry; Semi-arid climate